Control of Air Pressurizer Levels on Pressurized Water Reactor (PWR) with Fractional Order PID Control System - Rissa Damayanti; Abdul Halim; Syaiful Bakhri (JPSE (Journal of Physical Science and Engineering), 2020)
The water level control system in the pressurizer is carried out for safety purposes when the PWR reactor is operating. Control is done by maintaining the water level in the pressurizer at a certain level. The height of the water level in the pressurizer will change according to the conditions of the nuclear reactor. This research aimed to obtain the best safety control system using the fractional order PID (FOPID) control system and prove that using the control system will provide better results than other existing system applications. In this research, the optimum gain control of FOPID is obtained with Kp equals 416.4, Ki equals 416.4, Kd equals 104.1, constitutes integral equals 0.15, and derivative order equals 1.9, which results in 324 times faster settling time and maximum overshoot 1.5 times lower when compared to conventional PID controllers combined with CMAC.DOI: http://dx.doi.org/10.17977/um024v5i22020p071